Clinical effectiveness and cost-effectiveness of use of therapeutic monitoring of tumour necrosis factor alpha (TNF-ά) inhibitors [LISA-TRACKER® enzyme-linked immunosorbent assay (ELISA) kits, TNF-ά-Blocker ELISA kits and Promonitor® ELISA kits] versus standard care in patients with Crohn’s disease : systematic reviews and economic modelling /: systematic reviews and economic modelling. (November 2016) - Freeman, Karoline
No abstract available